Impact of a low-cost classroom dialogue-based intervention on preschool children's emotion understanding. Issue 5 (3rd September 2019) - Pons, Francisco; Giménez-Dasí, Marta; Daniel, Marie-France; Auriac-Slusarczyk, Emmanuèle; Businaro, Nicoletta; Viana, Karine
ABSTRACT: Children's emotion understanding has emerged as one of the best predictors of their psychological well-being, pro-social competences and school achievement. The main goal of this study was to evaluate for the first time the impact of an easy-to-use and not time-consuming classroom dialogue-based intervention (a) on preschool children's understanding of both simple and complex components of emotions and (b) on the range of individual differences in children's understanding of emotions. Participants were 112 typical 5-year-old children attending 10 different preschools in Canada and France. They were divided into an intervention group ( N = 55, 7 classrooms) and a control group ( N = 57, 7 classrooms). The intervention, The Tales of Audrey-Anne, lasted over 8–9 months (15 h in total) and was conducted in the classroom by the children's habitual teachers without previous training in using the intervention. Children were assessed before and after the intervention for their emotion understanding with the Test of Emotion Comprehension (TEC). Four results were found. First, the intervention had a positive impact on children's both overall and specific levels of emotion understanding. Second, it did not change the hierarchical order of the specific levels (i.e. external, mental and reflective). Third, it did not have an impact on the range of individual differences (considerable both before and after the intervention). Fourth, it had a positive impact on the longitudinal stability of these differences (much smaller for the children in the experimental group after the intervention). These findings are discussed in terms of the theoretical and applied implications.